Facilitating Work Integrated Learning (WIL) through Skills-Enabled E-Portfolios in Construction and Nursing : Final Report. - Williams, Anthony; Levett-Jones, Tracy; Sher, William; Simmons, Catharine; Bowen, Lynette (Office for Learning and Teaching, 2012)
Final report from a project which sought to identify the potential for the development of an e-portfolio system which could transcend disciplinary boundaries and provide meaningful documentation of work integrated learning (WIL) experiences of students from the disciplines of construction management and nursing. Such a portfolio could provide the means for disciplines to contextualise their portfolios and provide evidence of WIL activities. The project established what form the portfolio could take to obtain the best advantage of disciplinary contexts and to consider how the portfolio could be managed. The study demonstrated that there is considerable commonality between different disciplines. The synergies between them provide opportunities for a shared portfolio comprising a core set of requirements, supplemented with those that are discipline specific. The report includes a number of useful case studies from a range of institutions, including some outside the project team. These case studies, and other materials developed by the project are being assembled into a book and set of continuing professional development modules for distribution to the sector. Dissemination of the project's findings at conferences and through papers is also continuing.